Symbiodinium mitigate the combined effects of hypoxia and acidification on a noncalcifying cnidarian - Shannon G. Klein; Kylie A. Pitt; Matthew R. Nitschke; Samantha Goyen; David T. Welsh; David J. Suggett; Anthony R. Carroll (Global Change Biology, 2017)
Anthropogenic nutrient inputs enhance microbial respiration within many coastal ecosystems, driving concurrent hypoxia and acidification. During photosynthesis, Symbiodinium spp., the microalgal endosymbionts of cnidarians and other marine phyla, produce O 2 and assimilate CO 2 and thus potentially mitigate the exposure of the host to these stresses. However, such a role for Symbiodinium remains untested for noncalcifying cnidarians. We therefore contrasted the fitness of symbiotic and aposymbiotic polyps of a model host jellyfish ( Cassiopea sp.) under reduced O 2 (~2.09 mg/L) and pH (~ 7.63) scenarios in a full‐factorial experiment. Host fitness was characterized as asexual reproduction and their ability to regulate internal pH and Symbiodinium performance characterized by maximum photochemical efficiency, chl a content and cell density. Acidification alone resulted in 58% more asexual reproduction of symbiotic polyps than aposymbiotic polyps (and enhanced Symbiodinium cell density) suggesting Cassiopea sp. fitness was enhanced by CO 2 ‐stimulated Symbiodinium photosynthetic activity. Indeed, greater CO 2 drawdown (elevated pH ) was observed within host tissues of symbiotic polyps under acidification regardless of O 2 conditions. Hypoxia alone produced 22% fewer polyps than ambient conditions regardless of acidification and symbiont status, suggesting Symbiodinium photosynthetic activity did not mitigate its effects. Combined hypoxia and acidification, however, produced similar numbers of symbiotic polyps compared with aposymbiotic kept under ambient conditions, demonstrating that the presence of Symbiodinium was key for mitigating the combined effects of hypoxia and acidification on asexual reproduction. We hypothesize that this mitigation occurred because of reduced photorespiration under elevated CO 2 conditions where increased net O 2 production ameliorates oxygen debt. We show that Symbiodinium play an important role in facilitating enhanced fitness of Cassiopea sp. polyps, and perhaps also other noncalcifying cnidarian hosts, to the ubiquitous effects of ocean acidification. Importantly we highlight that symbiotic, noncalcifying cnidarians may be particularly advantaged in productive coastal waters that are subject to simultaneous hypoxia and acidification.